Microserfs - Coupland, Douglas (London : Harper perennial, 2004)
From the acclaimed author of Hey Nostradamus! comes a wonderful comic novel with `more one-liners than a decade of Woody Allen films' (Guardian), about the scramble for love and success in a brave new world...
ENH
STS International
Keywords: Computer software industry -- Employees -- Fiction; Young adults -- United States -- Fiction; Computer science